2022
DOI: 10.1590/1519-6984.239868
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular characterization of fluoroquinolone resistant Pseudomonas aeruginosa isolates in Palestine

Abstract: Fluoroquinolones are important antimicrobial agents for the treatment of Pseudomonas infections. A total of 11 isolates of P. aeruginosa were collected from different clinical samples from different medical centers in the North West Bank-Palestine during 2017. In this study, resistance to fluoroquinolones and secretions of β-lactamases were detected by phenotypic methods, while presence of β-lactamase gene sequences and other virulence factors were detected by PCR technique. PCR product for gyrA, parC and parE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…These were represented by missense mutations at position 83 (S83I/T/F) of the gyrA gene in addition to the mutation in the parC gene (S87L), where 82.8% (24/29) of the isolates harbored this mutation. Similar mutations in those positions of gyrA and parC , and QRDRs were reported among Pseudomonas isolates in Tunisia, 7 Palestine, 38 Estonia, 2 Iran, 33 , 39 , 40 South China, 41 USA, 42 Germany, 24 Japan, 43 , 44 and New Zealand. 45 …”
Section: Discussionsupporting
confidence: 73%
“…These were represented by missense mutations at position 83 (S83I/T/F) of the gyrA gene in addition to the mutation in the parC gene (S87L), where 82.8% (24/29) of the isolates harbored this mutation. Similar mutations in those positions of gyrA and parC , and QRDRs were reported among Pseudomonas isolates in Tunisia, 7 Palestine, 38 Estonia, 2 Iran, 33 , 39 , 40 South China, 41 USA, 42 Germany, 24 Japan, 43 , 44 and New Zealand. 45 …”
Section: Discussionsupporting
confidence: 73%
“…In contrast to the current findings, Rajaei et al 18 from Iran reported the ciprofloxacin as the most effective antibiotic against clinical P. aeruginosa isolates. In another study by Adwan et al 14 from Palestine who investigated 11 clinical P. aeruginosa isolates, 100.0 % of them were resistant against norfloxacin and ciprofloxacin. El-Badawy et al 13 who investigated seven quinolone antibiotics including nalidixic acid, ciprofloxacin, norfloxacin, ofloxacin, levofloxacin, gemifloxacin, and moxifloxacin against P. aeruginosa isolates, disclosed resistance rates ranging from 28.3% to 41.3%.…”
Section: Discussionmentioning
confidence: 98%
“…The qnr genes counteract with the blockage effects of quinolone antibiotics on the microbial enzymes such as topoisomerase II (DNA gyrase) and topoisomerase IV 10 . Other probable quinolone resistance mechanisms in P. aeruginosa include chromosomal mutations in quinolone resistance determining region (QRDR) of topoisomerase ( parC/parE ) and DNA gyrase ( gyrA / gyrB ) encoding genes, and mobile efflux pumps such as OqxAB 10 14 . Also, mutations of the regulatory genes that affect the permeability or efflux process are among the contributed quinolone resistance mechanisms 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of new resistance mechanisms may arise in vulnerable communities, leading to the dissemination of bacterial genes via conjugative plasmids (Meirelles-Pereira et al, 2002;Cerceo et al, 2016). Among the primary multi-drug resistant bacteria (MDRs), including species in the genera Bacillus, Pseudomonas, Acinetobacter, Klebsiella, and enterobacteria that are commonly found in hospital environments, water, soil, and food products (Logan, 2012;Smet et al, 2014;Ferreira et al, 2019;Arbab et al, 2021;Adwan and Omar, 2021). Food is a potential transmission source between the community and clinical settings (Carvalheira et al, 2021).…”
Section: Introductionmentioning
confidence: 99%